Initial Design of Dual-Axis Solar Tracker to Increase Efficiency of Monocrystalline Solar Panel Using Fuzzy Logic Method - Sin Euy Gun; Levin Halim; Faisal Wahab3 (Forum Pendidikan Tinggi Teknik Elektro Indonesia (FORTEI), 2020)
Fossils and mines become the main sources for producing the electricity in Indonesia. Due to availability of the sources, the price gets higher and it has a bad impact to the environment. Therefore, we need a new source to produce the electricity. A solar energy can be a solution, it has an unlimited availability and it’s eco-friendly. Solar panel can be a media to convert sun energy to electrical energy. Solar panel will be more efficient if the face of the panel always facing toward the sun. In this research, a panel will be designed so it can always move towards the sun movement. Fuzzy logic method will be use to the tracking method because it can increase the efficiency higher. Fuzzy logic systems consist of 4 input and 2 output. The inputs are based on each LDR sensor and the output is the motor on each axis. Based on the calculation horizontal has a 0,73% error and the vertical has 0,41%.